1998
DOI: 10.1097/00004647-199809000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Poly(ADP-ribosyl)ation after Focal Ischemia in Rat Brain

Abstract: Nitric oxide from neuronal cells plays detrimental roles in glutamate neurotoxicity and in focal brain ischemia. Nitric oxide directly damages DNA, and breaks in the DNA strands activate poly(ADP-ribose) polymerase (PARP), which brings poly(ADP-ribosyl)ation of the nuclear proteins. The excessive activation of PARP is thought to cause depletion of ATP and the energy failure resulting in cell death. To clarify the involvement of poly(ADP-ribosyl)ation in ischemic insult, we examined poly(ADP ribosyl)ation by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 18 publications
4
68
0
Order By: Relevance
“…in both experimental TBI and cerebral ischemia (Eliasson et al 1997;Endres et al 1997;Tokime et al 1998;LaPlaca et al 1999). Unique to the present study, protein nitration, a surrogate marker for the presence of the potent PARP-1 activator peroxynitrite, and poly-ADP-ribosylation, a biochemical footprint of PARP-1 activation, were evaluated for 21 days after CCI.…”
Section: Discussionmentioning
confidence: 99%
“…in both experimental TBI and cerebral ischemia (Eliasson et al 1997;Endres et al 1997;Tokime et al 1998;LaPlaca et al 1999). Unique to the present study, protein nitration, a surrogate marker for the presence of the potent PARP-1 activator peroxynitrite, and poly-ADP-ribosylation, a biochemical footprint of PARP-1 activation, were evaluated for 21 days after CCI.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not directly monitored NAD ϩ and ATP levels, such depletions occur in other models in which PARP inhibition protects from tissue damage. The protective paradigm of PARP inhibition after DNA damage has been demonstrated for numerous other models of cell death, including cerebral ischemia (10)(11)(12)(13)26), myocardial ischemia (27)(28)(29)(30), N-methyl-D-aspartic acid receptor-mediated excitotoxicity in the lung (31), methamphetamine neurotoxicity (32,33), and MPTP toxicity (34)(35)(36). In all of these cases, a lack of PARP activity, through either genetic disruption or pharmacologic inhibition, provides impressive protection from cell death after DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…As ATP is also consumed in efforts to resynthesize NAD ϩ , cells can die from energy loss. Cerebral ischemic damage is greatly diminished in mice with targeted deletion of PARP (PARP Ϫ͞Ϫ) (10,11) and in animals treated with PARP inhibitors (12,13). A role of PARP activation in pancreatic damage is also suggested by protection through PARP inhibition of pancreatic islet cells from NO-mediated killing (14,15).…”
mentioning
confidence: 99%
“…Excessive activation of poly(ADP-ribose) polymerase has been implicated to mediate cell death in different models of ischemia-reperfusion injury 10,40,42 as well as streptozotocininduced diabetes, 32 glutamate-induced neurotoxicity 5,49 and Alzheimer's disease. 27 The common feature in the pathogen- Figure 3 Poly(ADP-ribose) polymer immunohistochemistry on retinal sections to monitor PARP activation after ON transection with or without 3-ABA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, it has also been demonstrated that excessive PARP activation by various triggers resulting in depletion of NAD + and subsequent cellular ATP depletion ultimately leads to a necrotic-type cell death. 5,32,41,49 There is accumulating evidence that excessive PARP activation plays a key role in mediating ischemia-reperfusion-induced cerebral injury 10,11,38,42 and that infarct volume can be dramatically reduced by PARP inhibition and in PARP knock-out mice. 9,37,38 Cerebral ischemia results in massive activation of N-methyl-D-aspartat (NMDA) receptors via an increase of extracellular glutamate leading to elevated intracellular calcium concentrations, activation of neuronal NO synthase (nNOS), increased NO and ROS formation and ultimately to PARP-activating DNA damage.…”
Section: Introductionmentioning
confidence: 99%